The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00380-015-0634-8
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dissection related to retrograde cardioplegia cannula insertion

Abstract: Left atrial dissection (LAD) is a rare complication and is defined as a gap from the mitral or tricuspid annular area to the interatrial septum or left atrial wall. Because of its low incidence, this entity is not fully understood. LAD is related to mitral valve surgery as well as coronary artery disease, arrhythmia, trauma, and tumors, and occurs spontaneously. Transesophageal echocardiography is the most useful diagnostic modality for LAD, but multimodality investigation supports accurate diagnosis. We exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…LAD is a rare complication of cardiac surgery, associated with mitral valve surgery in 0.16-0.84% of cases [1,2]. Tsukui et al [1] reported a case of LAD related to retrograde cardioplegia cannulation, but they performed surgical treatment for the LAD. Other causes of LAD include insertion of left ventricular vent tube, aortic dissection, among others.…”
Section: Discussionmentioning
confidence: 99%
“…LAD is a rare complication of cardiac surgery, associated with mitral valve surgery in 0.16-0.84% of cases [1,2]. Tsukui et al [1] reported a case of LAD related to retrograde cardioplegia cannulation, but they performed surgical treatment for the LAD. Other causes of LAD include insertion of left ventricular vent tube, aortic dissection, among others.…”
Section: Discussionmentioning
confidence: 99%
“…LAD is a rare complication of cardiac surgery, associated with mitral valve surgery in 0.16-0.84% of cases. 1,2 Tsukui et al 1 reported a case of LAD related to retrograde cardioplegia cannulation, but they performed surgical treatment for the LAD. Other causes of LAD include insertion of left ventricular vent tube, aortic dissection, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 5% of all reported cases of LA dissection from 1979 to 2014 were associated with surgery involving the aorta, and only 2 reported cases to date involve retrograde cardioplegia cannulation of the coronary sinus (CS). [1][2][3] Here, we present a case of significant interest due to our direct visualization by transesophageal echocardiography (TEE) of the LA dissection point of entry at the CS, most likely caused by injury during retrograde cardioplegia catheter cannulation during a type-A aortic dissection repair. Such visualization has only been documented once before during a mitral valve repair.…”
Section: Glossarymentioning
confidence: 99%
“…Such visualization has only been documented once before during a mitral valve repair. 3 Additionally, we describe the clinical presentation of our patient and subsequent intraoperative management decisions and postoperative course.…”
mentioning
confidence: 99%